ARGUMENTASI YURIDIS PEMBERLAKUAN HUKUM KEPERDATAAN ISLAM DI INDONESIA - Natardi Natardi; Doli Witro (Institut Agama Islam Negeri Batusangkar, 2022)
The configuration of law enforcement in the religious courts has simply been implemented. When he has to deal with the law as a product of politics and the law as a product of fiqih studies, the choice is quite delegative. On the one hand, it meets the demands of empirical reality from the institutionalized wheel of life, while on the other hand, it goes hand in hand with the signalization text of the muqasid sharia. Although the work of the scholars as stated in the Compilation of Islamic Law (KHI) can be said to be a monumental work, it is still an outline that is impossible to complete in deciding every case faced. Therefore, this article discusses the implementation of Islamic civil law in Indonesia which is considered very appropriate to be applied to Muslims, without disturbing the national legal system and disturbing other people. This article aims to highlight the importance of implementing Islamic civil law in Indonesia with juridical arguments. The results of the analysis show that juridically in the current reform era, the implementation of Islamic civil law in Indonesia has shown a bright spot where many products of legislation related to it have been produced and practiced by Muslims. Based on MPR RI Decree Number IV/MPR/1999 concerning GBHN 1999-2004, Chapter IV, letter A, point 2, the implementation of Islamic civil law in Indonesia is the state’s obligation to uphold the rule of law (law enforcement). In practicing Islamic civil law by Muslims in Indonesia, there are still many obstacles and obstacles. Even though the rule of law has become a state decree, some individuals are not happy with Islam using this issue as one of their political motives.